The challenges of the implantation of Commum Curriculum National Basis on IFPR - Leão, Gabriel Mathias Carneiro; Rosset, Michele; Randi, Marco Antonio Ferreira (Revista Hipótese, 2018)
Considering the discussion on the implementation of a Common National basis for disciplinary program in basic education, different disciplinary programs in IFPR was annalized. The variety of matrices suggests the need for guidelines about curricular organization for the components of the common base in high school. If a common basis for disciplinary programs can guide discussions about curriculum, it can then limit their creativity freedom and the proposition of original ideas for education.